Breakfast Habits and Supplement Intake Among Health Sciences Students in Universiti Teknologi MARA, Selangor - Mohd Ramadan Ab Hamid, A.; Ummu Habibah Ahmad Mahauddin, B.; Norimah Said, C.; Aiman Nadia Akmar Rahman, D. (International Journal of Engineering and Technology, 2018)
There are high numbers of supplement usage among students with lack of knowledge regarding their side effects and health benefits. The purpose of this study is to assess the supplement usage and breakfast habits among undergraduate students. A total of 138 participants completed a questionnaire on breakfast habits and supplement usage. Less than half of the students consume supplements (34.8%). Most of the students consume supplement to improve energy and vitality (64.15%). Vitamin C is the most popular type of supplement consumed (79.5%). All students consume breakfast but 54.34% of them tend to skip breakfast due to lack of time (65.3%) and prefer to sleep longer (46.67%). The students also prefer to have ready to eat meals like bread, toast, hot drinks and cereal. Present findings propose empowering the nutrition education to increase knowledge on supplement and breakfast intake among students.Â Â